Geological and physical-chemistry characterization of asphaltite from Colombian Middle Magdalena region. (July 2020) - Bustos, N; Jerez, E; Paez, L; Roa, M
Abstract: The massive consumption of fossil hydrocarbons and the absence of new conventional oil reserves, research on unconventional resources is prevalent. The Asphaltite is a substance with high energy value thanks to its composition of high molecular weight hydrocarbons, becomes an energy alternative in the future. In Middle Magdalena region of Colombia, Luna formation emerges with its members Salada, Pujamana, and Galembo of Upper Cretaceous age, which contains a deposit of this type of substances, which can become an economic and energy engine for the region. A representative sample of this asphaltite was taken in the Galembo Member (Top of Luna formation) and a geological description was made about its formation and occurrence in the area. The solubility of asphaltite was evaluated in two characteristic solvents for hydrocarbons, toluene and heptane, the first of aromatic character, with which it was possible to solubilize probably corresponding to the light fractions, while solubilization with heptane generated a precipitate Asphaltene, a nature that was corroborated by tests of visible infrared and ultraviolet spectroscopy, additionally an elementary analysis was performed to determine the concentrations of carbon, hydrogen, sulphur and oxygen. Finally, by means of thermogravimetry and differential scanning calorimetry an analysis was carried out to evaluate its energy potential, according to the results obtained, asphaltite samples are a promising energy resource.